A One-Pot, Three-Component Synthesis of β,γ-Unsaturated α-Aminonitriles Using TMSCN as the Cyanide Source - Niu, Pengxian; Wen, Fei; Chen, Guangyuan; Liu, Tujun; Ding, Zhe (Synlett, 2025)
An efficient method for synthesizing β,γ-unsaturated α-aminonitriles via a one-pot procedure using cinnamaldehydes, anilines and trimethylsilyl cyanide (TMSCN) as starting materials under catalyst-free conditions is reported. This one-pot, three-component reaction proceeds efficiently with a broad range of substrates and tolerates a wide variety of functional groups. Notably, the process features a simple work-up procedure and does not require transition-metal catalysts. Additionally, the reaction can be performed on gram scale without loss of efficiency.
Keywords: α-aminonitriles; trimethylsilyl cyanide; cyanide source; catalyst-free; cinnamaldehyde